Attenuating mitochondrial dysfunction-derived reactive oxygen species and reducing inflammation: the potential of Daphnetin in the viral pneumonia crisis - Yuan, Yuan; Li, Runyuan; Zhang, Yinji; Zhao, Yuanxin; Liu, Qingqing; Wang, Jian; Yan, Xiaoyu; Su, Jing (Frontiers in Pharmacology, 2024)
Amidst the global burden of viral pneumonia, mitigating the excessive inflammatory response induced by viral pneumonia has emerged as a significant challenge. Pneumovirus infections can lead to the persistent activation of M1 macrophages, culminating in cytokine storms that exacerbate pulmonary inflammation and contribute to the development of pulmonary fibrosis. Mitochondria, beyond their role as cellular powerhouses, are pivotal in integrating inflammatory signals and regulating macrophage polarization. Mitochondrial damage in alveolar macrophages is postulated to trigger excessive release of reactive oxygen species (ROS), thereby amplifying macrophage-mediated inflammatory pathways. Recent investigations have highlighted the anti-inflammatory potential of Daphnetin, particularly in the context of cardiovascular and renal disorders. This review elucidates the mechanisms by which viral infection-induced mitochondrial damage promotes ROS generation, leading to the phenotypic shift of alveolar macrophages towards a pro-inflammatory state. Furthermore, we propose a mechanism whereby Daphnetin attenuates inflammatory signaling by inhibiting excessive release of mitochondrial ROS, thus offering mitochondrial protection. Daphnetin may represent a promising pharmacological intervention for viral pneumonia and could play a crucial role in addressing future pandemics.